The status of the question - survey of scientific productions related to the professional education of people with disabilities (Research, Society and Development, 2023)
The article brings a survey of scientific productions on the professional education of people with disabilities in Brazil. The objective of this investigation is to place researchers on the subject in question, amid a universe of academic publications, making a record of the themes, objectives and central idea, in addition to listing the postgraduate programs to which they are linked. The methodology used included qualitative research of the bibliographic type investigating the productions published in the Brazilian Digital Library of Theses and Dissertations – BDTD through the following descriptors: i. Professional Education, Disability and Federal Institute of Education; ii. Professional Education, Graduates and Federal Institute of Education; iii. Professional Education, Disability and the Labor Market. The survey was carried out between the months of September and October 2021, and no time frame was established for classifying the productions found. As a result of this article, 20 works were mapped directly linked to the subject suggested here, that is, they presented in their texts an intersection of information on professional education, people with disabilities and inclusion in the world of work. We conclude that the study carried out with the State of the Question indicates important clues for a more contextualized reflection on the professional education of people with disabilities, their insertion in the world of work and the implications of the current model of society in the development of inclusive processes, in addition to providing opportunities for an improvement of our object of study.